Durability of benefit after transcatheter tricuspid valve intervention: insights from actigraphy. (21st March 2022) - Stocker, Thomas J.; Cohen, David J.; Arnold, Suzanne V.; Sommer, Saskia; Braun, Daniel; Stolz, Lukas; Hertell, Helene; Weckbach, Ludwig T.; Wild, Mirjam G.; Doldi, Philipp; Orban, Martin; Orban, Mathias; et al.
Abstract : Aims: Tricuspid regurgitation (TR) is associated with high mortality, morbidity and reduced physical capacity. This study was designed to examine the long‐term impact of transcatheter tricuspid valve intervention (TTVI) on physical activity by using the method of actigraphy. Methods and results: Overall, we prospectively included 128 heart failure patients with severe TR (median age 79 years, 48% female) who were scheduled for TTVI. Patients were equipped with activity tracking devices for 1 week before TTVI, and again at 1–6 months and 1 year after TTVI. We compared continuous physical activity (CPA), defined as the mean number of steps/day with New York Heart Association class, quality of life assessments, and 6‐min walk distance (all p <0.01). TTVI reduced TR to grade ≤2+ in 94% of patients. Median (interquartile range [IQR]) CPA at baseline was 3108 (1350–4959) steps/day, which increased by 31.4% to 3958 (1823–5657) steps/day at 1–6 months and 4080 (2293–6514) steps/day at 1 year after TTVI ( p <0.001 for both comparisons). The impact of TTVI was significantly higher in advanced heart failure patients with low baseline activity (baseline CPA <1350 steps/day; 1‐year CPA increase: +121.3%; p <0.001), when compared to moderate activity patients (baseline CPA 1350–4959 steps/day; 1‐year CPA increase: +27.5%; p <0.01) or high activity patients (baseline CPA >4959 steps/day; 1‐year CPA change: +2.6%; p = 0.39). Conclusion: One‐week actigraphy demonstrates durable improvement of physical activity after TTVI. Fragile chronic heart failure patients with very low baseline activity, as determined by actigraphy in this study, significantly benefit from transcatheter intervention and should not be excluded from TTVI. Abstract : Actigraphy demonstrates durable improvement of physical activity in heart failure patients with underlying significant tricuspid regurgitation after transcatheter tricuspid valve intervention.